Savage, Your Spirits Walk Beside Us - The Politics Of Black Religion - Pasquier, Michael (Teaching History: A Journal of Methods, 2009)
Today it is common to hear people speak of the "African American community" and the "Black Church" as if they were cohesive, clearly-defined institutions. Barbara Dianne Savage, professor of history at the University of Pennsylvania, looks at the complex history of such terms in her book Your Spirits Walk Beside Us: The Politics of Black Religion, effectively chronicling the debates of African Americans over the role of religion in political activism and social reform in twentieth-century America. Specifically, Savage identifies three "paradoxes" present at "the nexus between black religion and black politics," namely, the rich diversity and idiosyncratic manifestations of religion among individual African Americans that elude clear demarcation, the largely localized and decentralized organization of predominantly African American churches that confound any notion of an all-inclusive Black Church, and the tendency within African American churches toward male leadership and female dominance.